Prevention of cruelty to animals act, 1960 - Professional Book Publication (Delhi: Professional Book Publication, 2023)
Prevention of cruelty to animals act, 1960 as amended by The Jammu and Kashmir reorganization Act, 2019.
Keywords: The Jammu and Kashmir reorganization Act, 2019.; Bare Act